ANALISIS STAKEHOLDERUNTUK DESAIN PROGRAM PENGEMBANGAN SDM RESPONSIF GENDER BIDANG ESDM - Rohmatulloh; Retno Kusumastuti; Julian Ambassador Shiddiq (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2018)
The purpose of this literature review is to discuss the concept of stakeholder analysis and its application to design the model of gender-responsive human resources development program at Education and Training Agency for Energy and Mineral Resources. The use of stakeholder analysis in program design is to provide information on mapping the interests, influences, and strategies of its participation. By optimally participating in program design, the stakeholder is expected to get much support in implementing the program. The application of stakeholder analysis into the program design of gender-responsive human resource development shows the number of identified twenty stakeholders from internal and external. It is analyzed by using the interest and influence matrices in four quadrants, ie players, subjects, crowds, and context setters. The participation strategies used in this study are adjusted to each stakeholder position: 1) players and context setters with information delivery and consultation strategies, 2) subjects with engagement and joint strategies, and 3) crowds with collaborative or empowerment strategies. This analysis information is used as input for the program planning team to design the program according to the needs and interests of all parties.